The problem of alienation in the digital age in the context of D. V. Pivovarov's concept of synthetic paradigm - V. I. Kudriavtseva; E. S. Lebed; Yu. V. Tsiplakova (Интеллект. Инновации. Инвестиции, 2024)
Social networks, messengers, online platforms and artificial intelligence have become an integral part of our daily lives. Communication now takes place in hyperreality, through digital mediators, which actualizes the discourse of alienation in modern society.